Matemática fundamental e conceitos de astronomia para alunos do 6º ano - SANTOS, Rosana Cardoso dos (2022)
Astronomy is a vast field that views the betterment of human beings as constituents of a vast universe. Research and knowledge in the field of astronomy are increasingly indispensable tools in our daily lives. Therefore, the need to transmit knowledge effectively to elementary school students becomes extremely important. In this way, this work proposes the relationship between mathematics and astronomy, as a form of multidisciplinary interaction, with the objective of exercising the application of mathematical concepts, worked on in the 6th year of Elementary School, with the objective of analyzing the difficulties of contents related to astronomical and mathematical activities through the sundial activity in 6th grade elementary school classes. In the development of this study, some of the history and interaction between these two disciplines stood out. For this, activities were developed that show how the concepts worked in each of these areas can be used in the school education process of elementary school students. In the course of this work, it was possible to evaluate the extent to which subjects related to astronomy and new technologies are of interest to students, concluding that it is advantageous to use them as catalysts for the construction of mathematical scientific knowledge. Another factor observed was that as students embrace the learning process, the development of their skills and abilities occurs naturally.